2016
DOI: 10.1158/1538-7445.sabcs15-p4-13-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P4-13-06: Results of the 3rd interim analysis of the non-interventional trial BRAWO – Subanalysis of patients <70 years and ≥ 70 years

Abstract: Background BRAWO is a German non-interventional study of 3000 patients (pts) with advanced/metastatic, hormone-receptor-positive and HER2-negative breast cancer treated with everolimus and exemestane (EVE+EXE). The pivotal BOLERO-2 trial demonstrated that adding EVE to EXE improved PFS over EXE and was generally well tolerated in elderly patients with HR+ advanced breast cancer (>65 years as well as >70 years). Here we describe data of elderly patients treated with EVE+EXE in daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The present study and BOLERO-2 showed similar overall rates for other AEs of interest: nausea (35% versus 31%), decreased appetite (31% versus 31%), weight loss (27% versus 28%), anemia (21% versus 21%), hyperglycemia (17% versus 14%), and pneumonitis (15% versus 16%) [9]. Rates of these AEs were considerably lower in the BRAWO study [14].…”
Section: Discussionsupporting
confidence: 67%
“…The present study and BOLERO-2 showed similar overall rates for other AEs of interest: nausea (35% versus 31%), decreased appetite (31% versus 31%), weight loss (27% versus 28%), anemia (21% versus 21%), hyperglycemia (17% versus 14%), and pneumonitis (15% versus 16%) [9]. Rates of these AEs were considerably lower in the BRAWO study [14].…”
Section: Discussionsupporting
confidence: 67%
“…The conclusion was that the everolimus-exemestane treatment had a manageable safety profile in the elderly patients and was consistent with that reported previously in BOLERO-2 and BALLET. 32 Lower patient age (74 years) was significantly associated with a longer duration of treatment. 32…”
Section: Everolimus and Safety: Selection Of Patients In Abcmentioning
confidence: 98%
“…32 Lower patient age (74 years) was significantly associated with a longer duration of treatment. 32…”
Section: Everolimus and Safety: Selection Of Patients In Abcmentioning
confidence: 98%
See 1 more Smart Citation
“…Individual patient characteristics such as age, preference, treatment history, and disease status-in addition to efficacy, safety, convenience, cost, and availability-will continue to influence treatment decisions, pending new evidence informing patient selection and optimal sequencing. There is a need for ongoing research in this area, including noninterventional, prospective, real-world observational studies such as the German BRAWO [51] and the Canadian Treat ER1ight [52] studies. To inform standards of care, correlative research aimed at identifying biomarkers predictive of preferential benefit, optimal sequencing, or both is an important ongoing avenue of research.…”
Section: Et Therapy Optimal Sequencingmentioning
confidence: 99%